Pengembangan Wearable Robotic Arm Input dan Virtual Instrument untuk Pengendalian dan Pemantauan Lengan Robot - Ekaputra, I Made Wicaksana; Setiawan, Joga Dharma (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2017)
This paper investigate the integration of wearable robotic arm input (WRAI) with virtual instrument (VI) for controlling and monitoring the manipulator. The WRAI was designed by following the contours of human arms and equipped with five potentiometers as the sensor. The sensors were placed properly on WRAI by considering the ergonomic aspect. Each sensor on WRAI actuate each joint on the manipulator. The manipulator has five degrees of freedom (DOF) which consists of five revolute joints. For monitoring process, control panel of VI was created suitably by LabVIEW, and its block diagram was mainly programmed by following the forward kinematics approach. The VI obtains the input signal from the rotation of potentiometer on WRAI, and then transmitted to the receiver on manipulator to actuate the joints. By monitoring the control panel, the user can observe each angle joint on manipulator and also the position and orientation of end effector. The test results show the WRAI performs good controllability and ergonomic. The WRAI can control the manipulator easier than using remote control and joystick. Further, the control panel of VI is able to simplify the monitoring process by the friendly user interface.